Juridical study on the implementation of business strategy on group construction companies (holding companies) holding companies from business law perspectives - Zai Syahril Nur; Dyah Permata Budi Asri; Murjiyanto Murjiyanto (Kajian Hasil Penelitian Hukum, 2020)
The implementation of business strategies by Construction Holding Company in business diversification is very vulnerable to violations of Business Competition Law. Violations of business competition by Group Companies / Holding Companies are very crucial Business Competition Law issues. Conflicts of interest in business diversification connected with the jurisdiction of state sovereignty are a polemic of Business Competition Law. The occurrence of Monopolistic Practices and Unfair Competition by the Holding Company against the business world in a country is a violation of the law and contrary to the Business Competition Law. As for knowing the Implementation of Holding Company Business Strategy to Avoid Violation of Business Competition Law and Implementation of Business Competition Law against Prevention of Violations in the Implementation of Business Strategy in Holding Company Companies. From these problems the authors conducted research using normative juridical methods that emphasize the legal norms and laws and regulations and analyzed using descriptive qualitative methods. From the results of research and analysis it can be concluded that the Implementation of Business Strategy on Construction of holding must be guided by the law of business competition and apply good corporate governance and comply with it and carry out with ethics and morality. KPPU embodies business competition law against Prevention of Violations in the Implementation of Business Strategy in the business world by means of advocacy, consultation, namely by developing compliance programs with business competition law such as seminars / outreach and executive forums. In this way it is hoped that business actors, stakeholders and stakeholders can understand and disseminate knowledge in the business world.